Remarkable lives. Lizzie Hehir in conversation with Jerome Carson. Issue 3 (31st August 2020) - Hehir, Lizzie; Carson, Jerome
Abstract : Purpose: The purpose of this paper is to provide a profile of Lizzie Hehir. Lizzie tells her own story and is then interviewed by Jerome. Design/methodology/approach: This series of papers used the case study approach. However, each paper is written collaboratively, using the person's own words. The deeply individual nature of each person's story reminds us of the complexities of working in mental health. Findings: In her account, Lizzie tells us of her long-term battles with self-harm. It was a struggle that she eventually won. Research limitations/implications: Individual stories allow us to access people's lived experience with mental illness. No diagnostic manual can ever truly categorise this uniqueness. Practical implications: Lizzie shows it is possible to overcome self-harm though she still experiences something of the trauma she went through when she has triggers. Social implications: When we see burns victims, we seldom approach them asking them how they sustained their injuries, but as Lizzie points out, many people feel able to ask people who have self-harmed about their injuries. Originality/value: Lizzie writes with conviction and humility. Now working in mental health, she is able to reach out to others who are as troubled as she once was.